GROWTH RESPONSE AND CATION - INTERACTION IN HIPPOPHAE RHAMNOIDES L (Journal of Sciences, Islamic Republic of Iran)
The interaction between sodium and calcium, magnesium and calcium and the combined effect of sodium, magnesium and calcium was observed on the growth and ion uptake of Hippophae rhamnoides L. The results demonstrated that an addition of sodium with calcium, (set a, Na 2.5 + Ca 5 mM) showed prominent increase in fresh weight of roots and shoots. The dry weight (average) of roots decreased and that of shoots increased but the percent dry weight of both roots and shoots decreased following an increase in percent water content. An addition of magnesium with calcium, (set b, Mg 2.5 + Ca 5 mM) showed an increase in fresh and dry weight (average and percentage of root and shoot), while percent water content decreased. The addition of sodium and magnesium with calcium , (set c, Na 2.5 +Mg 2.5 + Ca 5 mM) showed an increase in fresh and dry weight (average) of roots and shoots, while percentage dry weight of roots decreased and that of shoots increased and the percentage water content of roots increased and that of shoots decreased. The treatments of sets a, b and c increased the uptake of all ions studied. However, a difference in ion uptake within treatments occurred. It appears that the presence of calcium mitigates the adverse effects of sodium and magnesium by preventing their uptake and enhances the uptake of potassium